Cascade-free predictive adhesion control for IPMSM-driven electric trains - Ren, Jiao; Li, Ruiqi (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The application of active adhesion control to the traction control system of an electric train holds great appeal for maximizing longitudinal acceleration force. Most of the currently reported works regulate the adhesion between wheel and rail by adjusting the torque reference of a cascade motor drive controller, which suffers from slow speed response and excessive start torque. This article proposes a cascadefree predictive adhesion control strategy for electric trains powered by an interior permanent magnet synchronous motor (IPMSM) to address these issues. The proposed control scheme utilizes an improved perturbation and observation method to predict the time-varying wheel-rail adhesion state and determine the optimal slip speed. The initial setpoint reference command from the driver master is then adjusted to a dynamic reference that continuously adapts to the predicted adhesion conditions. Finally, the predictive speed control method is employed to ensure rapid convergence of the tracking objective. The simulation and hardware-in-the-loop testing results confirm that this approach achieves excellent dynamic performance, particularly during the train start-up phase and in the high-speed weak magnetic area of the IPMSM.